A Note on Treatment of Signals in Digital Signal Processing and in Network Calculus - Andrzej Borys (Scientific Journal of Gdynia Maritime University, 2019)
This short paper presents from the perspective of the operator theory some basic operations performed on signals in the digital signal processing as well as in the network calculus. These are the following operations: signal sampling, amplitude quantization, and signal recovery from its samples – in the digital signal processing. And regarding the network calculus, building up an auxiliary (continuous) traffic flow and recovery of a real traffic that possesses a non-continuous structure (with some granularity) after manipulations that were carried out with the use of a flow model are discussed in this paper. Some interesting results achieved and interpretations regarding the aforementioned stuff are presented.